2014
DOI: 10.1093/brain/awt371
|View full text |Cite
|
Sign up to set email alerts
|

The Gdap1 knockout mouse mechanistically links redox control to Charcot–Marie–Tooth disease

Abstract: Mutations in the mitochondrial fission factor GDAP1 are associated with severe peripheral neuropathies, but why the CNS remains unaffected is unclear. Using a Gdap1−/− mouse, Niemann et al. demonstrate that a CNS-expressed Gdap1 paralogue changes its subcellular localisation under oxidative stress conditions to also act as a mitochondrial fission factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 58 publications
3
68
0
Order By: Relevance
“…However, other groups have challenged this model, suggesting instead that deletion of Mfn2 increases ER-mitochondrial association and, in turn, are questioning whether Mfn2, indeed, localizes to the ER (Filadi et al, 2015;Cosson et al, 2012). Regardless of the role Mfn2 has in ER-mitochondrial contacts, the importance of mitochondrial fusion proteins -particularly in neuronal cells -is highlighted by the fact that hypomorphic mutations in Mfn2 are most often responsible for autosomal dominant Charcot-Marie-Tooth (CMT) disease, axonal, type 2A2 (CMT2A2) (Chapman et al, 2013;Misko et al, 2012;Niemann et al, 2014;Yu-Wai-Man et al, 2011), a common peripheral neuropathy (Züchner et al, 2004), whereas mutations in Opa1 are the most common cause of hereditary blindness, i.e. autosomal dominant optic atrophy (ADOA) (Yu-Wai-Man et al, 2011;Alexander et al, 2000;Zanna et al, 2008).…”
Section: The Mitochondrial Fission and Fusion Machinerymentioning
confidence: 99%
“…However, other groups have challenged this model, suggesting instead that deletion of Mfn2 increases ER-mitochondrial association and, in turn, are questioning whether Mfn2, indeed, localizes to the ER (Filadi et al, 2015;Cosson et al, 2012). Regardless of the role Mfn2 has in ER-mitochondrial contacts, the importance of mitochondrial fusion proteins -particularly in neuronal cells -is highlighted by the fact that hypomorphic mutations in Mfn2 are most often responsible for autosomal dominant Charcot-Marie-Tooth (CMT) disease, axonal, type 2A2 (CMT2A2) (Chapman et al, 2013;Misko et al, 2012;Niemann et al, 2014;Yu-Wai-Man et al, 2011), a common peripheral neuropathy (Züchner et al, 2004), whereas mutations in Opa1 are the most common cause of hereditary blindness, i.e. autosomal dominant optic atrophy (ADOA) (Yu-Wai-Man et al, 2011;Alexander et al, 2000;Zanna et al, 2008).…”
Section: The Mitochondrial Fission and Fusion Machinerymentioning
confidence: 99%
“…3). The exact role of GDAP1 in peroxisomal and mitochondrial fission is not yet clear but it is able to promote fission and requires DLP1 and Mff to act on mitochondria and peroxisomes [60,111]. Mutations in GDAP1 have been associated with Charcot-Marie-Tooth disease, the most common inherited peripheral neuropathy.…”
Section: The Dlp1 Recruitment Factorsmentioning
confidence: 99%
“…N-terminal autosomal recessively inherited disease mutations which impact on mitochondrial fission do not alter peroxisomal fission suggesting differences in mechanism [60]. Recent studies have suggested a role for GDAP1 and other GDAP1-like proteins in the response to oxidative stress associated with an increase in reduced glutathione levels [111] or a possible function in organelle movement via interaction with organelle trafficking proteins RAB6B and caytaxin [125]. In addition, a role for GDAP1 in mitochondria-ER interactions is suggested [4,60].…”
Section: The Dlp1 Recruitment Factorsmentioning
confidence: 99%
“…These features are also present in the GDAP1-paralogue GDAP1like1, possibly constituting a new class of GST proteins13. In response to changes in the cellular redox state, the cytosolic GDAP1like1 translocates to mitochondria, integrates into the MOM and causes mitochondrial fission17. This translocation and integration of GDAP1like1 into the MOM is specifically caused by an increase in the concentration of the oxidized form of glutathione in vitro and in vivo where it is capable of substituting for the loss of GDAP1 in the central nervous system of GDAP1-deficient mice17.…”
mentioning
confidence: 99%
“…In response to changes in the cellular redox state, the cytosolic GDAP1like1 translocates to mitochondria, integrates into the MOM and causes mitochondrial fission17. This translocation and integration of GDAP1like1 into the MOM is specifically caused by an increase in the concentration of the oxidized form of glutathione in vitro and in vivo where it is capable of substituting for the loss of GDAP1 in the central nervous system of GDAP1-deficient mice17. Interestingly, mitochondrial translocation from the cytosol under oxidative stress conditions has previously been described also for other GSTs such as GSTA4–4 and GSTPi18192021.…”
mentioning
confidence: 99%